The role of physical culture in the life of students of secondary vocational education - G. A. Litvina; N. V. Makhnovskaya; S. V. Kasyanov; V. E. Kulchitsky (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. Physical culture is an organic part of human culture, its special independent sphere. It actively aﬀects the vital systems of the human body, which were obtained in the form of makings and develop in the process of vital activity under the inﬂuence of the environment. At its core, physical culture has an appropriate motor activity in the form of physical exercises that allow you to eﬀectively form the necessary physical abilities and optimize health.Goal. The main tasks of physical education are highlighted, the beneﬁts of physical education classes while studying at the GBOU in the SSPI at the faculty of Vocational Education and Training. The problems that students of secondary vocational education may face in physical education classes are noted.Materials and methods. The research is based on general scientiﬁc methods: the method of system analysis, comparison, deductive method, inductive method. The research is based on psychological methods: observation, conversation, psychological modeling, diﬀerential.Results and discussion. In the course of the work, it was found that 52 % of respondents noted the positive impact of knowledge on physical culture on the process of maintaining and strengthening their physical and psychological health. However, 9 % of the surveyed secondary school students believe that physical activity does not play an important role in maintaining health.Conclusion. Based on the results of the study, it can be concluded about possible ways to improve the quality of these classes. The system of theoretical and practical experience of students of the Faculty of secondary vocational education in physical education classes is also considered. The current trends in the creation of additional programs are outlined, taking into account all regional conditions, professional orientation in which GBOU IN SSPI is located. Physical education contributes to the development of a wide range of students' skills: personal and social. They learn to accept a variety of responsibilities and roles, including leadership, coaching, and judging. Through the experience that physical education oﬀers, students learn to be competitive, creative and be prepared for diﬃcult situations.